2014
DOI: 10.1111/1462-2920.12611
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐active bacteriophages from the Baltic Sea ice have diverse genomes and virus–host interactions

Abstract: Heterotrophic bacteria are the major prokaryotic component of the Baltic Sea ice microbiome, and it is postulated that phages are among their major parasites. In this study, we sequenced the complete genomes of six earlier reported phage isolates from the Baltic Sea ice infecting Shewanella sp. and Flavobacterium sp. hosts as well as characterized the phage-host interactions. Based on the genome sequences, the six phages were classified into five new genera. Only two phages, 1/4 and 1/40, both infecting Shewan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 73 publications
5
43
0
Order By: Relevance
“…These phages were assigned to the viral families Siphoviridae and Myoviridae and showed great specificity to the host strain . Again, like the study of Holmfeldt et al (2013), genomic analysis of six of these bacteriophages showed that they belong to five different and newly proposed genera (Senčilo et al 2014).…”
Section: Bacteriophagesmentioning
confidence: 87%
See 1 more Smart Citation
“…These phages were assigned to the viral families Siphoviridae and Myoviridae and showed great specificity to the host strain . Again, like the study of Holmfeldt et al (2013), genomic analysis of six of these bacteriophages showed that they belong to five different and newly proposed genera (Senčilo et al 2014).…”
Section: Bacteriophagesmentioning
confidence: 87%
“…Variability in environmental conditions might also help to explain the high diversity of viruses that infect the same host that have been isolated at different places and/or time points (Holmfeldt et al 2007;Martínez et al 2015). The genome analyses revealed that most of the Baltic Sea viruses are unique and belong to previously unknown genera or even form new families (Attoui et al 2006;Holmfeldt et al 2013;Senčilo et al 2014). Comparative (meta)genomics in parallel with experimental studies can help further elucidation of links between phage specificity, infection strategy (lysis vs. lysogeny) and environmental gradients in the Baltic Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Among the enzymes directly involved in DNA replication, ORF104 encodes a DNA ligase containing Adenylation_kDNA_ligase_like domain (cd07896), shows homology to DNA ligase in Shewanella sp. phage 1/4 (YP_009100328.1) [24]. ORF118 encodes a DNA helicase containing a PIF1 domain (pfam05970), shows [28].…”
Section: Discussionmentioning
confidence: 99%
“…Putative portal protein encoded by ORF141 with a length of 505 amino acids shows 57% identity with portal protein in Shewanella sp. phage 1/4 (YP_009100417.1) [24]. The portal protein is a key functional component of the capsid for DNA packaging and genome encapsidation [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation